Improving Students’ Combinatorial Thinking Ability through Numbereds Head Together - Rustam E. Simamora; Doni Andriyan Zunaiedy (Study Program of Mathematics Education of Unimed Postgraduate Program, 2021)
Combinatorics is a branch of mathematics that is very important, but this topic has not received serious attention in educational research compared to other branches of mathematics such as geometry, calculus and algebra in Indonesia. Meanwhile, in secondary and undergraduate education, existing research reports that students’ combinatorial thinking ability tend to be low. Efforts to improve students’ combinatorial thinking ability in one of the Vocational Schools in Medan, Indonesia, are carried out through the development of the Numbered Heads Together (NHT). NHT is one cooperative learning structure. The result showed that NHT learning improved students’ combinatorial thinking ability.Keywords: combinatorics, combinatorial thinking ability, numbered heads together